FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SATUAN KERJA BADAN LAYANAN UMUM UNIVERSITAS RIAU - Fahdi, Muhammad; Sari, Ria Nelly (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This study aimed to examine the effect of the quality of human resource, utilizationof information technology, leadership styles, organizational culture, internal controlunit, and organizational commitment to the performance of public service agencyworking unit Riau University. Research conducted on 94 financial management atthe University of Riau. Respondent participation rate amounted to 70.21% (66people). The analysis tool used is multiple regression with SPSS version 21. Testsperformed include testing the validity and reliability, testing data and classicalassumptions of normality, the coefficient of determination, and hypothesis testingresearch. The results showed that the higher the quality of utilization of informationtechnology, leadership styles and organizational commitment will affect theperformance. Meanwhile, human resource , organizational culture, and the internalcontrol unit has no effect on the performance exhibited significantly. The coefficientof determination was 50,9%, which is still contained 49,1% explained by otherfactors that are not included in this study.Keywords: Performance, Public Service Agency